Reflexions sobre la categorització del «Cançoner satírich valencià» de Miquel i Planas - Martínez Romero, Tomàs (Caplletra. Revista Internacional de Filologia, 2003)
This article identifies the ambitions and literary motifs of the various works in the «Cançoner» and questions the concept of “satire” for defining them as a whole. Considering the transgressions contained in it as a literary product with no subversive aim clears the way for viewing it as a set of cleverly combined elements of satire, parody and burlesque, following on from compositions like the «Col·loqui de dames» (Ladies’ Dialogue), and allowing different parodical readings from amorous and Boccaccian points of view.